HUBUNGAN MOTIVASI DAN PERILAKU MANUSIA DALAM BERINOVASI - Telly Pauline Ulviana Siwi (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Innovation is a potential that is very meaningful for one's life. Through innovation, a person will be able to find ways to solve the problems they face effectively and efficiently so that they are more likely to succeed in the future. The purpose of this study will look at the relationship between motivation and human behavior with innovations carried out in organizations or work. Based on research that has been done, the hypothesis that states there is a positive relationship between motivation in innovation can be accepted. Motivation contributed 28.78% to innovate. This means that the higher the motivation, the higher the innovation. The hypothesis which states that there is a positive relationship between human behavior / self-concept can be accepted in innovation. Human behavior / self-concept contributes to innovation by 40.58%.